Cognitive Resources Moderate the Relationship Between Pro-Environmental Attitudes and Green Behavior. Issue 9 (November 2020) - Langenbach, Benedikt P.; Berger, Sebastian; Baumgartner, Thomas; Knoch, Daria
Given the urgency of climate change mitigation, motivating individuals to behave in sustainable ways constitutes a key challenge for environmental science. Although many studies evidence people's long-lasting pro-environmental attitudes, such attitudes often do not translate into behavior. The present research hypothesizes that cognitive resources are a crucial moderator, explaining when pro-environmental attitudes turn into behavior. Specifically, we investigate the attitude–behavior gap while taking a "cognition perspective" on environmental behavior. Using experience sampling, the present research demonstrates that individual differences in central aspects of cognitive control (assessed by working memory capacity) moderate the relationship between environmental attitudes and behavior. Our correlational findings suggest that people with positive environmental attitudes also require high working memory capacity to behave in line with their ideals. Our results do not only provide empirical support for recent theorizing in environmental research, but, perhaps more importantly, might offer a central lever for behavioral change initiatives (e.g., "nudging").